Problematic issues of using modern information and other technologies in the implementation of investigator’s and interrogator’s instructions by operational units - O. O. Zahumennyi (Law and Safety)
The problematic issues of using modern information and other technologies in the implementation of investigator’s and interrogator’s instructions by operational units are considered. The purpose of the article is to study and identify problematic issues and develop proposals and recommendations for improving the use of information and other modern technologies by employees of operational units in carrying out the instructions of the investigator and interrogator in criminal proceedings. The main tasks are to develop appropriate proposals and recommendations on how to solve the identified problems at the theoretical and legislative levels and in law enforcement. The specifics and importance of the organization of interaction between bodies and units during the pre-trial investigation, as well as the specifics of the use of modern information and other technologies are considered. Such interaction is defined as coordinated cooperation of persons involved in criminal procedural legal relations, whose activities are regulated by laws and other departmental regulations and which it is necessary to achieve the objectives of specific criminal proceedings, and aimed at discussing the results and planning further measures. It is concluded that the importance of cooperation between the authorities during the pre-trial investigation is to ensure targeted and effective measures aimed at rapid, complete and impartial investigation, as well as resolving the case on the merits. The Criminal Procedure Code of Ukraine does not contain a list or definition of certain technical means that are legally required or recommended for use in the execution of orders, and does not detail certain aspects of procedural design based on the results of their implementation. In the conduct of any investigative (searching) activities in practice, in fact, either technical devices and tools or information technology are used in the sense in which they are proposed in the Code and which cause difficulties in use, especially modern latest information technology in the form of computing hardware and software. It is concluded that the appropriate use of modern information technology, open network resources, government or commercial databases, as well as modern approaches to the implementation of the instructions of investigators and interrogators significantly speed up the pre-trial investigation, as operational units have the opportunity to obtain information in a short period of time, using the capabilities of innovative modern technologies. According to the results of the study, specific proposals and recommendations for improving the use of information and other